The Influence of Motivation, Time Management, Self-Efficacy, And Social Support on the Academic Achievement of Activist Students Participating in Student Organizations (ORMAWA) at Universitas Muhammadiyah Surakarta - Evita Ayu Septiyaningrum; M. Farid Wajdi (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to analyze the influence of motivation, time management, self-efficacy, and social support on the academic achievement of activist students active in student organizations (ORMAWA) at Universitas Muhammadiyah Surakarta. Employing a quantitative descriptive approach, this research involves ORMAWA-affiliated activist students as respondents. Primary data were collected through a Likert scale questionnaire covering motivation, time management, self-efficacy, social support, and academic achievement variables. Data analysis was performed using Structural Equation Modeling (SEM) with SmartPLS software to assess validity, reliability, and the influence of independent variables on academic achievement. The findings indicate that these four variables contribute significantly, accounting for 70.3% of students' academic achievement in ORMAWA. This result underscores the importance of developing motivation, time management skills, self-efficacy, and social support to enhance students' academic success. Universities are encouraged to offer relevant programs to improve students' soft skills. This study contributes to the literature and provides opportunities for further research by adding variables and expanding the sample.